A Literature Review on the Experience of Long-Term Mental Illness. (3rd June 2018) - Collier, Elizabeth; Grant, Maria J.
ABSTRACT: Purpose : To illuminate long-term experiences of mental illness from both research and autobiographical accounts. Design : A literature review of English-language papers, 1950–2014, relating to the experience of long-term mental illness indexed in AgeInfo, AMED, ASSIA, British Nursing Index (BNI), CINAHL, MEDLINE, PsycEXTRA, and PsychINFO. Findings : Twenty-five research papers and nine autobiographic accounts met the review criteria. Thematic analysis revealed nine themes: fear, explanation seeking, stigma, disability, coping strategies, control, support, change and learning, and life history. Specific gaps of note relate to age differences, acknowledgement of longevity of mental illnesses, and different cultural perspectives. Research Implications : There is an absence of longitudinal studies focused on experiences of long-term mental illness. The considerable length-of-time implicated in the experiences suggests that more individual life experience rather than illness focused studies are needed, enabling a holistic understanding. This includes studies from cultures other than the Western world. Greater transparency is needed in justifying age inclusions or passive exclusion of older peoples' perspectives. Practical Implications : Knowledge of long-term mental illness experiences is of great importance to mental health practitioners. Evidence-based services cannot be provided if we do not have an holistic understanding of long-term mental illness. Social Implications : This review questions our ability to provide effective support for those experiencing long-term mental illness, in particular older people and different cultural perspectives. Originality/Value : There appear to be no literature reviews that focus on the individual experience of long-term mental illness. It highlights the surprisingly small number of research studies available to inform mental health practitioners.